2015
DOI: 10.1007/s00417-015-2958-6
|View full text |Cite
|
Sign up to set email alerts
|

Central serous chorioretinopathy fundus autofluorescence comparison with two different confocal scanning laser ophthalmoscopes

Abstract: The two types of FAF images of CSC showed different lesion brightness before and after CSC resolution but demonstrated similar lesion composite patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Near-infrared (NIR) OCT (787 nm) provided better visualization of the subretinal and choroidal structures than the light of the shorter red laser wavelengths used in the Optos 200TxTM imaging system (633 nm). All participants were imaged with pseudocolor, simulated white light (488-633 nm) and green light (GAF) autofluorescence (532 nm) on UWF imaging [17].…”
Section: Methodsmentioning
confidence: 99%
“…Near-infrared (NIR) OCT (787 nm) provided better visualization of the subretinal and choroidal structures than the light of the shorter red laser wavelengths used in the Optos 200TxTM imaging system (633 nm). All participants were imaged with pseudocolor, simulated white light (488-633 nm) and green light (GAF) autofluorescence (532 nm) on UWF imaging [17].…”
Section: Methodsmentioning
confidence: 99%
“…All participants were imaged with multicolor, simulated white light (488-633 nm) and green light (GAF) auto uorescence (532 nm) on UWF imaging [17].…”
Section: Methodsmentioning
confidence: 99%
“…1 Precise measurement of the VF is important in the disease and is usually performed using a static automated perimeter, such as the Humphrey Field Analyzer (HFA; Carl Zeiss Meditec, Dublin, CA, USA). 2,3 Recent reports have suggested that fundus autofluorescence (FAF) imaging provides an objective measurement of the accumulation of lipofuscin in the retina in various retinal diseases, including age-related macular degeneration, central serous chorioretinopathy, 4,5 and RP. 6,7 In eyes with RP, a characteristic FAF ring is often observed in the macular region, suggesting the accumulation of lipofuscin at the level of the retinal pigment epithelium.…”
mentioning
confidence: 99%